Generative AI in practice 100+ amazing ways generative artificial intelligence is changing business and society - Marr, Bernard (John Wiley & Sons, Inc., 2024)
"Generative AI isn't just the biggest trend right now; it's the pinnacle of today's technological evolution. Beyond the capabilities of ChatGPT and similar AIs that can generate written content and artwork, GenAI is rewriting the rulebook. From crafting intricate industrial designs, writing computer code, and producing mesmerizing synthetic voices to composing enchanting music and innovating genetic breakthroughs, the horizons are limitless. Picture a world where your daily news is read by your favorite celebrity, where video games conjure unparalleled universes in real-time, where machines concoct groundbreaking medicines, and where literature and courses are tailored flawlessly for you. Dive into the future with GenAI. In "Generative AI in Practice," renowned futurist Bernard Marr offers readers a deep dive into the captivating universe of GenAI. This comprehensive guide not only introduces the uninitiated to this groundbreaking technology but outlines the profound and unprecedented impact of GenAI on the fabric of business and society. It's set to redefine all our jobs, revolutionize business operations, and question the very foundations of existing business models. Beyond merely altering, GenAI promises to elevate the products and services at the heart of enterprises and intricately weave itself into the tapestry of our daily lives"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on April 22, 2024)
Keywords: Artificial intelligence -- Economic aspects; Artificial intelligence -- Social aspects; Intelligence artificielle; Aspect économique; Intelligence artificielle; Aspect social